MENU ENGINEERING SEBAGAI STRATEGI PENETAPAN PRODUK MAKANAN DALAM MENGHADAPI TATANAN KEHIDUPAN BARU DI KORI RESTAURANT & BAR KUTA - BALI - Bagus Putu Ekadharma Susila; Surya Nugraha (Badung: LPPM Universitas Triatma Mulya, 2021)
This study aims to analyze the menus at Kori Restaurant & Bar, Kuta - Bali in the period June - December 2019. The results of this analysis are one of the references in determining food products in facing the new order of life during the covid19 pandemic. The results of the menu analysis showed that the appetizer group (appetizer) with the category of plowhorse as many as 3 items, 4 items star, 2 items of dog and 1 item of puzzel. The menu in the salad dish group with the plowhorse category is 2 items, the star is 3 items and the puzzle is 1 item. The menu in the soup (soup) group with the category of plowhorse, star and dog each has 1 item. Main course menu (main dish) in the International sub-group with 2 items of plowhorse, 15 items of star, 2 items of dog and 1 item of puzzle. Hamburger sub-group with 1 item plowhorse category, 2 star items and 1 item puzzle. Main Course from Bali sub-group with 4 items plowhorse category, 3 star items, 1 dog item and 2 puzzle items. Menu in the dessert group with 2 items of plowhorse category, 6 star items, 1 item of dog and puzzle each. The decisions and follow-ups that will be taken are maintaining the menu, changing menu prices, improving